Brief resolved unexplained events: Retrospective validation of diagnostic criteria and risk stratification. Issue 1 (14th December 2018) - Colombo, Marco; Katz, Eliot S.; Bosco, Annalisa; Melzi, Maria L.; Nosetti, Luana
Abstract : Background and Objectives: This study retrospectively evaluated the AAP guidelines for diagnosis and risk stratification of Brief Resolved Unexplained Events (BRUE) in a well‐characterized cohort of infants admitted with an Apparent Life Threatening Event (ALTE). Further, using prospective follow‐up, we endeavored to determine the safety of implementing ambulatory care for the lower risk BRUE population (LR‐BRUE) and estimate the cost‐savings of this practice. Methods: Retrospective application of the BRUE criteria on infants younger than 12 months of age who had been admitted with an ALTE from 2006 to 2016 at a single tertiary care center in Lombardy, Italy. ALTE patients were classified into three groups; (1) Not a BRUE; (2) Lower‐risk (LR)‐BRUE; and (3) Higher‐risk (HR)‐BRUE. Patients were contacted prospectively to obtain long‐term follow‐up outcomes and medical records and billing databases were reviewed. Results: Among the 84 infants admitted for an ALTE, 35 (42%) were not a BRUE, 16 (19%) were a LR‐BRUE, and 33 (39%) were a HR‐BRUE. Only one of the LR‐BRUE patients had a subsequent LR‐BRUE event, and was later diagnosed with a seizure disorder. Two HR‐BRUE babies had also previously presented with a LR‐BRUE. Application of the LR‐BRUE guidelines would have decreased health expenditure by 20%. There were no deaths or significant morbidities in either BRUE group. Conclusions: Applying the recent AAP BRUE guidelines and risk stratification to a well‐characterized cohort of admitted ALTE patients is a safe and cost‐effective approach. Careful out‐patient follow‐up is recommended as one of our patients with a LR‐BRUE had a recurrence, and was subsequently diagnosed with a seizure disorder.